Building a research model for mobile prepaid phone cards: An evidence of Telkomsel in Bengkulu - Marnisah L.; Ali N.; Zamzam F.; Setiawan H.; Samsurizal (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The growth of telecommunication companies has led to competition in getting the customers to buy their data plan through the purchase of prepaid card. However, little is known on the factors that influence mobile phone users decision to purchase prepaid card. This study aims to examine the effects of product quality, promotional strategy, and price on the intention to purchase prepaid car, which can be used by prepaid card providers to attract more users in purchasing prepaid card for their mobile phones. An online survey method was used to collect data, and 123 questionnaires were properly completed and submitted by mobile phone users in the Telkomsel mobile telecommunication market. Data was tested using a PLS-based Structural Equation Modeling (SEM). The results of this study indicate that there is a positive and significant effect on product quality, promotional strategy and price on purchase intention. BEIESP.